“It Feels Weird Telling You For Sure”: Ambivalence and Uncertainty about Academic Integrity in International Students’ Self-Reports of Using Paid Academic Support Services - Heng Hartse, Joel (Canadian Perspectives on Academic Integrity, 2023)
This presentation reports on a study that examines some international undergraduate students’ use of private academic support services (PASS), a growing phenomenon in Canadian higher education in the last decade whose practitioners often advertise to international and/or multilingual students. We situate the use of PASS at the intersection of three constructs: literacy brokering (Curry and Lillis, 2006), contract cheating (Lancaster & Clarke, 2016), and private supplementary tutoring/“shadow education” (Bray, 2008), seeking to understand why some students choose to pay for help with academic work and how they understand the ethics of their choices. Using a survey (n = 898 international student responses, with ⅔ being self-identified as users of English as an additional language) and semi-structured follow-up interviews (n= 23), this presentation addresses the following research questions: What is the type and nature of PASS that some students use, and why do they seek such services? How do students understand the use of PASS in relation to academic integrity? Survey results reveal 30% of participants described using some form of PASS, most commonly “homework help” websites or tutoring. Students described a variety of reasons for seeking PASS, often related to their perceived convenience and/or limited access to other forms of in-time support. Interviews revealed ambivalence about the use of PASS; while some reported feeling PASS were helpful in achieving academic goals, some described feeling uneasy or uncertain about their ethical acceptability or usefulness. We conclude with policy and pedagogical implications for this growing grey area of para-academic support.